EXPERIMENTS ON ARTIFICIAL PROPAGATION OF HILSA, TENUALOSA ILISHA (HAMILTON) - Sen, P R; De, D K; Nath, D (Indian Journal of Fisheries, 2011)
The note presents the results of successful rearing of hilsa larvae under captivity for four months.Artificial propagation of hilsa was tried by many workers (Wilson, 1909; Raj, 1917;Southwell and Prashad,1918; Kulkarni, 1950) but none succeeded in rearing the resultant hatchlings beyond three days. Malhotraet ah (1969,1970 and 1979) successfully bred the fish by stripping the fresh-water stocks of hilsa availablefrom Ganga at Sirsa, 50 km downstream of Allahabad. They were also successful in rearing thehatchlings for a longer period. Panicker et al. (1982) achieved limited success in the direction of propagatinghilsa in Vallab Sagar (Ukai) reservoir at Gujarat. Bhanot and De (1984) reared hilsa fry obtainedfrom fresh-water stretch of Hooghly river in freshwater pond for more than 2 years and the growth attainedby the fish was found to be highly satisfactory.